Privacy‐preserving federated learning based on multi‐key homomorphic encryption. Issue 9 (17th January 2022) - Ma, Jing; Naas, Si‐Ahmed; Sigg, Stephan; Lyu, Xixiang
Abstract: With the advance of machine learning and the Internet of Things (IoT), security and privacy have become critical concerns in mobile services and networks. Transferring data to a central unit violates the privacy of sensitive data. Federated learning mitigates this need to transfer local data by sharing model updates only. However, privacy leakage remains an issue. This paper proposes xMK‐CKKS, an improved version of the MK‐CKKS multi‐key homomorphic encryption protocol, to design a novel privacy‐preserving federated learning scheme. In this scheme, model updates are encrypted via an aggregated public key before sharing with a server for aggregation. For decryption, a collaboration among all participating devices is required. Our scheme prevents privacy leakage from publicly shared model updates in federated learning and is resistant to collusion between k < N − 1 participating devices and the server. The evaluation demonstrates that the scheme outperforms other innovations in communication and computational cost while preserving model accuracy.